Analysis of pandanus extracts by reversed phase high performance liquid chromatography / Hannis Fadzillah Mohsin …[et al.] - Mohsin, Hannis Fadzillah; Jalal, Ratni Suriyani; Wahab, Ibtisam Abdu; Zulkifli, Abdul Rasyid; Sadiran, Muhammad Faxrurrazy (Universiti Teknologi MARA Shah Alam, 2016)
The Pandanus species (Pandanaceae family) was investigated, in order to set up a library of their chromatographic profiles. From a literature review, the most common Pandanus plant that was greatly examined was P. amaryllifolius (the fragrant screw pine), followed by P. sanderi. Here, the chromatographic data from an extract of a relatively unfamiliar Pandanus is also presented. The leaves of P. monotheca were extracted by using methanol. Later, the extract was filtered, prior to a Reversed-Phase High Performance Liquid Chromatography (RP-HPLC) experiments. The automated system was set to run by gradient elution (acetonitrile:water). The flow rate was maintained at 1 ml/min, otherwise stated in a number of attempts. The ultra-violet absorbance of the Pandanus’ constituents was measured via Multiple Wavelength Detector. From the chromatogram, the major peaks for Pandanus’ compounds were eluted (λ = 220, 260 and 360 nm) and the retention times were recorded. The lower absorbance readings of other minor peaks could be due to various minor secondary metabolites, such as the furolignan. The different elution time depends on the polarity of the composition. In short, Pandanus’ phytochemicals could be obtained via alcoholic extraction. The utilisation of modern chromatographic applications enables the scientists to discover and subsequently, purify single component of the complex natural mixtures. This finding can be beneficial to the research areas in botanical study, pharmacognostical assessment and biotechnology industry. It is aimed that more Pandanus species could be learnt for the future